Does the Platform Matter? - Alice Binder; Tobias Frey; Thomas N. Friemel (University of Zurich, IKMZ - Department of Communication and Media Research, 2023)
Cannabis is one of the most common substances consumed among adolescents and research demonstrates that exposure to cannabis-related content online is associated with cannabis consumption. However, little is known about the relationship between exposure on different social media platforms and the role of personal characteristics such as sensation seeking. We conducted a cross-sectional study among 1,309 adolescents between 15 and 19 years old in Switzerland investigating the relationship between exposure to cannabis-related content on Instagram, Snapchat, and TikTok and the intention to consume cannabis.  Results suggest a positive link between exposure to cannabis-related content on Instagram and the intention to consume cannabis. No such link emerged regarding Snapchat or TikTok. Additionally, we found a positive relationship between adolescents' sensation seeking and the intention to consume cannabis. Moreover, we found that high sensation seekers' exposure to cannabis-related content on Snapchat is positively related to the intention to consume cannabis. In sum, this study shows that not only the platform matters when discussing the effects of cannabis-related online content but also personal characteristics such as sensation seeking.